2020
DOI: 10.1007/s10694-020-01031-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fuel Bed Width on Upslope Fire Spread: An Experimental Study

Abstract: In this work, a series of experiments across a porous fuel bed of pine excelsior with two sidewalls were conducted under different slope and fuel bed width conditions. It was observed that the fire line stayed straight during fire spread after the initial line ignition for all tests. Flame length and rate of spread (ROS) increased with increasing slope angle or fuel bed width. A dimensionless correlation of ROS was developed that integrated the effects of slope and fuel bed width. For a lower slope angle (£ 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Li et al [92] Upslope Increased in the slope significantly increased the radiative heat and rate of fire spread.…”
Section: Madadgar Et Al [84]mentioning
confidence: 98%
See 1 more Smart Citation
“…Li et al [92] Upslope Increased in the slope significantly increased the radiative heat and rate of fire spread.…”
Section: Madadgar Et Al [84]mentioning
confidence: 98%
“…The rate of increase in upslope flame propagation is due to an increase in radiant and convective heat flux between the slope and flame. Also, Li et al [92] examined the upslope effects on fire propagation using experimental analysis. The study revealed that an increased upslope increased the rate of the fire spread, and radiative heat flux was mainly responsible for preheating.…”
Section: Topographymentioning
confidence: 99%
“…After the pre-experiment, a 0.5-m long precombustion area was determined. When the fire heads passed through the precombustion area, the fire spread rate reached the 'seemingly steady state,' and at this time, the measurement of the fire spread rate was started (Li et al 2021). To measure the rate of fire spread, 20 thermocouples are placed along the centreline of the combustion bed at intervals of 0.1, 0.5 m from the igniting end; each thermocouple position was 0.5, 0.6, 0.7, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.9, 2.0, 2.1, 2.2, 2.3, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4 m. The time for each thermocouple's temperature to reach 254°C was extracted, and this was called the igniting point for P. koraiensis.…”
Section: Laboratory Combustion Experimentsmentioning
confidence: 99%
“…Garnica et al [6] evaluated the effects of wind speed, temperature, humidity, and other environmental factors on fire behavior via prescribed burning and explored the optimal conditions for prescribed burning in Mexican pine and oak forests. Other studies have focused on the mechanisms of fire spread at different wind speeds, moisture contents, slopes, and other conditions [7][8][9][10][11][12] and the statistical analysis of forest fire behavior characteristics based on a large number of burning experiments [13][14][15][16][17]. The advantage of measuring fire behavior characteristics through prescribed burning and laboratory burning experiments is that we can obtain accurate fire behavior data and other factors of fire environments and fuel while approaching fire lines.…”
Section: Introductionmentioning
confidence: 99%